Ungulate use of an at-grade fauna passage and roadside animal detection system: A pilot study from Southern Sweden - Bhardwaj, Manisha; Erixon, Filippa; Holmberg, Isak; Seiler, Andreas; Håkansson, Emma; Elfström, Marcus; Olsson, Mattias (Frontiers in Environmental Science, 2022)
Wildlife-vehicle collisions (WVC) cost millions of euros each year in loss of life and damages. Wildlife crossing structures and fencing are commonly implemented mitigation strategies to reduce WVC and increase landscape connectivity for wildlife. Typically, crossing structures are over- or under-pass structures that allow animals to safely cross the road, while separating them from the road and traffic. An alternative strategy could be an at-grade fauna passage coupled with a Roadside Animal Detection System (RADS). At-grade fauna passages are designated locations where a gap in fencing allows animals to cross over the road, while RADS alert drivers of animals at the upcoming passage, so that they can adjust their driving behaviour accordingly and avoid collisions. In this pilot study, we investigated the use of one at-grade fauna passage by roe deer (Capreolus capreolus), red deer (Cervus elaphus) and wild boar (Sus scrofa) in southern Sweden, and compared changes in the number of WVCs before, during and after the construction of the passage. We collected a total of 326 wildlife crossings from 722 individuals over 1 year of monitoring (24 January 2020–24 January 2021). We found that crossing events tended to be dominated by the time animals spent in the roadside verge from which they approached the at-grade fauna passage, particularly for roe deer that spent a lot of time browsing in the roadside verge during dusk. We also found that animals spent longer in the passage if vehicles were present. In our 1 year of surveys, we only recorded three accidents, and when comparing the annual collision statistics before, during, and after construction of the at-grade fauna passage, we demonstrated an overall reduction in collisions by 66%. While our pilot only evaluates a single site, it does provide promising preliminary results that suggest that at-grade fauna passages can help in efforts to reduce collisions, while maintaining connectivity over medium-sized roads for large ungulates.